Facilitating Trade in Services - Hoekman, Bernard (World Bank, Washington, DC, 2020)
In 2016, the Government of India proposed negotiations on an agreement to facilitate trade in services to complement the 2013 World Trade Organization Trade Facilitation Agreement in goods. The proposal did not find much support, but plurilateral talks launched in 2017 on various policy areas encompass areas that are very relevant from a services trade facilitation perspective. This paper argues that participating in the current plurilateral talks can do much to achieve services trade facilitation objectives by identifying good regulatory practices. Although elements relevant to services trade facilitation are on the table in the World Trade Organization, there are important gaps. Identifying priorities for complementary international cooperation to facilitate trade in services on a plurilateral basis requires initiatives that bring together governments, services industry associations, and sectoral regulators.